RETRACTED: Cathodic electrodeposition of RuO2 thin films from Ru(III)Cl-3 solution (Retracted article. See vol. 226, pg. 387, 2019) - Park, BO; Lokhande, CD; Park, HS; Jung, KD; Joo, OS (ELSEVIER SCIENCE SA, 2004)
Ruthenium oxide (RuO2) films of different thicknesses have been cathodically deposited on titanium substrates under galvanostatic condition from aqueous acidic Ru(III)Cl-3 Solution. The deposition conditions and structural properties of these films have been studied. The X-ray diffraction (XRD) and transmission electron microscopy (TEM) studies revealed that as-deposited RuO2 film is nanocrystalline. The scanning electron microscopy (SEM) study showed that RuO2 film is porous and the surface morphology changes with film thickness. (C) 2004 Published by Elsevier B.V.
Keywords: HYDROUS RUTHENIUM OXIDE; CYCLIC VOLTAMMETRIC DEPOSITION; METAL-OXIDES; TITANIUM; COMPOSITES; TRANSITION